How to prepare for Logical reasoning for cat - "Sharma, Arun" (New Delhi, 2017)
This comprehensive new book, solely devoted to Logical Reasoning (LR) will effectively equip aspirants to tackle all possible types of questions that can be asked on this topic in CAT and other similar higher level competitive examination. In the new format of the CAT Question Paper, Logical Reasoning (LR) is one of the vital components. There are now only two sections in the CAT Paper. In this scenario, LR forms a critical part of the Verbal Ability and Logical Reasoning Section. A good score in this segment would take you closer towards your goal of succeeding. It is therefore essential to develop your problem-solving skills in LR to a level where you can quickly and comfortably attempt the LR questions. Besides, LR also forms an important component of other prestigious non-CAT MBA entrance examinations.
Keywords: Psychology